Letter (copy) : War work: rates of wages and Spanish relief - Tewson, Vincent
032-0013-001 Spanish Relief Secretary's HVT/FC/KA/66 28th June 1940 Mr. H. Campbell, 184 Battlefield Road, Langside, Glasgow. Dear Mr. Campbell, WAR WORK - RATES OF WAGES I thank you for your letter referring to the above subject. I may say that we have written to Mr. Cornwell, giving him such particulars as is possible. We explained by cable that as rates vary from district to district and between job and job, it was not possible to cable details. Spanish Relief. You will remember that when you were here, you mentioned the question of the money which Mr. Cornwell had in hand for Spanish relief. We have now received a cable from him stating that he has forwarded this money. The draft is, of course, not to hand, but I thought you would like to know what is transpiring on this. Yours sincerely, Assistant Secretary. 292/946/32/13